2011
DOI: 10.1016/j.chom.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Binding Enables Botulinum Neurotoxin B to Sense Low pH for Translocation Channel Assembly

Abstract: SUMMARY Botulinum neurotoxins (BoNTs, serotypes A-G), elaborated by Clostridium botulinum, can induce lethal paralysis and are classified as category-A bioterrorism agents. However, how BoNTs translocate from endosomes into the cytosol of neurons to gain access to their intracellular targets remains enigmatic. We discovered that binding to the ganglioside GT1b, a toxin co-receptor, enables BoNT/B to sense low pH, undergo a significant change in secondary structure, and transform into a hydrophobic oligomeric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 52 publications
(71 reference statements)
8
85
0
Order By: Relevance
“…Similar results were recently reported for BoNT/B (Sun et al, 2011). For BoNT/A, LC translocation is observed as a time-dependent increase in Na + conductance through the HC channel; the initial 14 pS channel activity rapidly transitions through several intermediate before reaching a stable approximately 68 pS Montal, 2007a, 2007b).…”
Section: Minimal Protein Translocation Unitsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results were recently reported for BoNT/B (Sun et al, 2011). For BoNT/A, LC translocation is observed as a time-dependent increase in Na + conductance through the HC channel; the initial 14 pS channel activity rapidly transitions through several intermediate before reaching a stable approximately 68 pS Montal, 2007a, 2007b).…”
Section: Minimal Protein Translocation Unitsupporting
confidence: 74%
“…3) (Fischer et al, 2008). A similar requirement for BoNT/B has recently been presented by Sun et al (2011). Sun et al (2011) further suggested that, for BoNT/B, RBD association with its ganglioside receptor promotes channel formation through oligomerization.…”
Section: Productive Intoxication Requires Several Steps Of Interdomaimentioning
confidence: 83%
See 1 more Smart Citation
“…TeNT Undergoes Secondary Structural Changes in the Presence of Polysialogangliosides at Low pH-Recent studies demonstrated that interaction of ganglioside GT1b with BoNT/B and BoNT/E triggers conformational changes within the two proteins that facilitates transformation into hydrophobic proteins at low pH (34,35). To test whether gangliosides trigger a similar conformational change in TeNT, CD spectroscopy was performed at neutral and acidic pH in the absence and presence of GT1b.…”
Section: Functional Entry Of Recombinant Tetanus Toxin and Proteinmentioning
confidence: 99%
“…Besides, it is not easy to predict the structural and conformational changes induced both in the molecule and at the membrane surface (at various stages), making it difficult to assert any strong assumptions regarding the role of various domains and the receptors involved. This has been proved repeatedly where new receptors and factors influencing toxin internalization are identified (59)(60)(61)(62) with an increased understanding of the toxinhost interaction. It is really necessary to confirm the data obtained from such studies in vivo before making any strong interpretations.…”
Section: Discussionmentioning
confidence: 99%